Characteristics and Outcomes of Very Elderly Enrolled in a Prehospital Stroke Research Study. Issue 11 (November 2016) - Sanossian, Nerses; Apibunyopas, Kathleen C.; Liebeskind, David S.; Starkman, Sidney; Burgos, Adrian M.; Conwit, Robin; Eckstein, Marc; Pratt, Frank; Stratton, Sam; Hamilton, Scott; Saver, Jeffrey L.
Abstract : Background and Purpose—: Greater numbers of individuals aged ≥80 years enjoy a high quality of life, yet historically stroke trials have excluded this population. We aimed to describe a population of very elderly successfully enrolled into an acute stroke trial and compare their characteristics and outcomes with the younger cohort. Methods—: We analyzed consecutive patients enrolled <2 hours of symptom onset in a prehospital stroke treatment trial, the FAST-MAG clinical trial (Field Administration of Stroke Therapy-Magnesium). We gathered demographic, treatment, and outcome data for nonelderly (<80 years old), very elderly (≥80 years old), and extreme elderly (≥90 years old). We describe key differences in the population of elderly and the impact of their inclusion on the clinical trial. Results—: Of 1700 participants in FAST-MAG, there were 1210 nonelderly, 490 very elderly, and 60 extreme elderly subjects. Very elderly stroke patients successfully enrolled in a research study were more likely to be women, white, and have an ischemic mechanism rather than an intracerebral hemorrhage. Although the very elderly had generally poorer outcomes, 4 in 10 were functionally independent at 90 days. Conclusions—: Inclusion of the very elderly population in acute stroke clinical trials would both significantly increase study participation and generalizability of future acute stroke clinical trials. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00059332. Abstract : Supplemental Digital Content is available in the text.